(untitled) (Global Journal of Medical Research, 2017)
Posterior reversible encephalopathy syndrome (PRES) usually presents with rapid onset of neurologic symptoms with characteristic vasogenic oedema in imaging studies. PRES is most importantly associated with hypertension and kidney disease. We describe a case of PRES in a 13-year-old female patient who presented with normal vital signs, neurological symptoms, oliguria, and laboratory test results consistent with thrombotic thrombocytopenic purpura (TTP). Head computed tomography (CT) scan revealed subtle hypodensity in the white matter of the right parietal lobe, strongly suggesting PRES, with multiple hemorrhagic foci in the right frontal lobe and right basal ganglia. Aggressive TTP treatment was initiated; however, she developed rapidly progressive glomerulonephritis and renal failure. Twelve days since presentation, she developed severe acute respiratory distress, which resulted in death. Therefore, PRES need not be a complication; it can be the presenting sign of an undiagnosed disease and a high index of suspicion is required in such cases.